Health‐related quality of life in idiopathic pulmonary fibrosis: Data from the Australian IPF Registry - Ian Glaspole; Sally Chapman; Wendy A. Cooper; Samantha Ellis; Nicole Goh; Peter Hopkins; Sacha Macansh; Annabelle Mahar; Yuben Moodley; Eldho Paul; Paul N. Reynolds; E. Haydn Walters; et al. (2017)
Studies analysing the effect of worsening pulmonary physiological impairment in idiopathic pulmonary fibrosis (IPF) with respect to quality of life have been limited to single centres or highly selected trial populations. The aim of this study was to determine the principal determinants of baseline and longitudinal health-related quality of life (HRQoL) in a large unselected IPF population.We used the Australian IPF Registry to examine the relationship between HRQoL, measured using the St George Respiratory Questionnaire (SGRQ), and demographic features, physiological features, co-morbidities and symptoms. Linear regression analysis was performed to identify predictors of baseline HRQoL, linear mixed model analysis to determine the effect of time and forced vital capacity (FVC) on SGRQ and Cox proportional hazards regression to examine the relationship between HRQoL and all-cause mortality.Baseline data from 516 patients were available (347 males; mean (SD) age: 71.3 ± 8.6 years). Univariate analysis showed significant associations between HRQoL and demographic, clinical and physiological features. However, multivariate analysis demonstrated independent associations only between SGRQ and dyspnoea (University of California San Diego Shortness of Breathlessness Questionnaire (UCSD-SOBQ); R2 = 0.71, P < 0.0001), cough severity (visual analogue scale; R2 = 0.06, P < 0.0001) and depression (Hospital Anxiety and Depression Scale; R2 = 0.04, P < 0.0001). Linear mixed-effects modelling of combined baseline and longitudinal data confirmed these associations, as well as for FVC% predicted (P = 0.005). Multivariate Cox proportionate-proportional hazards regression analysis demonstrated no association between HRQoL and risk of mortality.Cough, dyspnoea and depression are major symptomatic determinants of HRQoL in IPF. FVC decline is associated with worsening HRQoL.